The Inverse Solution Of Dexterous Robot By Using Neural Networks - Kazem, Bahaa Ibraheem; Hadi, Samer Yahya (Al-Khwarizmi Engineering Journal, 2007)
The inverse kinematics of redundant manipulators has infinite solutions by using conventional methods, so that, this work presents applicability of intelligent tool (artificial neural network ANN) for finding one desired solution from these solutions. The inverse analysis and trajectory planning of a three link redundant planar robot have been studied in this work using a proposed dual neural networks model (DNNM), which shows a predictable time decreasing in the training session. The effect of the number of the training sets on the DNNM output and the number of NN layers have been studied. Several trajectories have been implemented using point to point trajectory planning algorithm with DNNM and the result shows good accuracy of the end effector position for the desired trajectory.